The Role of Return on Assets on Stock Prices and Tax Aggressiveness Food and Beverage Companies - Pujiati, Desi; Misdiyono, Misdiyono (Universitas Gunadarma, 2025)
The food and beverage industry is one of the five leading sub-sectors in the non-oil and gas management industry. One of the factors that influences stock prices is the company's internal factors. Internal factors can be seen through the company's future performance projections. Tax aggressiveness is an action to reduce the company's tax burden by legal (tax avoidance) or illegal (tax evasion) means to optimize the company's profits. This study aims to analyze the role of Return On Asset on tax aggressiveness and stock prices in food and beverage sub-sector companies on the Indonesia Stock Exchange for the 2019-2023 period. The method used is quantitative with the analysis tool used, namely simple linear regression analysis. The results of the study indicate that Return On Asset in food and beverage sub-sector companies on the Indonesia Stock Exchange for the 2019-2023 period plays a role in changes in stock prices. Return On Asset has no role in companies carrying out tax aggressiveness. The results of the adjusted R-square show that changes in stock prices can be explained by a greater increase in the Return on Asset ratio than by the aggressive tax practices carried out by the company.